2019
DOI: 10.1109/access.2019.2955556
|View full text |Cite
|
Sign up to set email alerts
|

State Estimation Approach of Lithium-Ion Batteries by Simplified Ultrasonic Time-of-Flight Measurement

Abstract: This work presents an approach to monitoring the State-Of-Charge of Lithium-Ion battery cells via piezo disc-based ultrasonic Time-Of-Flight measurement by measuring the traveling time of a mechanical pulse through the cell between two surface-mounted sensors. The main advantage of this approach is the simplicity and the resulting low cost, which makes it suitable for future application in battery management systems. In detail, the excitation of the piezo actuator is done using a single semiconductor switch in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Ultrasonic battery monitoring is a well-established method of obtaining feature rich data from a battery. Each battery, regardless of chemistry or design, undergoes redistribution of density as a function of charge along with bulk moduli changes in anode and cathode layers [6], [7] . Many studies now exist that use ultrasound to exploit this, as well as the monitoring of battery ageing [8] , gassing [9] and swelling [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic battery monitoring is a well-established method of obtaining feature rich data from a battery. Each battery, regardless of chemistry or design, undergoes redistribution of density as a function of charge along with bulk moduli changes in anode and cathode layers [6], [7] . Many studies now exist that use ultrasound to exploit this, as well as the monitoring of battery ageing [8] , gassing [9] and swelling [10] .…”
Section: Introductionmentioning
confidence: 99%
“…For obtaining ultrasonic signal readings, in many studies, a probe was fixed to the surface of the battery with glue or a clamp. 17,23,25,26,33,36 Although it is easy to carry out, but the influences of external stresses cannot be avoided. In addition, sound wave needs a medium to propagate if probe does not touch the surface of battery.…”
Section: A Noncontact and Transmissionreflection Combined Multichanne...mentioning
confidence: 99%
“…22 The state differences of internal materials can be analyzed on the basis of the signal transmission changes in acoustic waves within a battery as ultrasonic detection is highly sensitive to material properties. 1 Gold et al, 23 Hsieh et al, 24 Popp et al, 25 Kim et al, 26 Ladpli et al, 17,27 Wu et al, 28 Zhao et al, 29 Copley et al, 30 Song et al 31 and Bommier et al 32 found that the time of flight (TOF) results of ultrasonic signal had linear relationships with the state of charge (SOC) and state of health (SOH) during charging and discharging of the battery. Moreover, Bhadra et al 22 tracked ultrasonic transmission signal with respect to the discharge process under different current rate and identified a direct correlation between changes in the acoustic waves and the physical transitions of active materials.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the energy storage technologies, lithium-ion batteries (LIBs) are the most commonly used ones because of their inexpensive manufacturing costs and easier maintenance in smaller size. LIBs, comparing to the other technologies, have longer life cycles, higher rate of charge/discharge, and high energy density, resulting in large capacity suitable for industrial use cases [7,8]. In contrast to their many advantages, LIBs require a reliable condition monitoring system to monitor their state of health (SoH) and state of charge (SoC) due to the safety and operational issues associated with them.…”
Section: Introductionmentioning
confidence: 99%